2018
DOI: 10.1002/pen.25017
|View full text |Cite
|
Sign up to set email alerts
|

Formation of polypropylene/functional graphene oxide nanocomposites with Different FGs loading in elongation flow condition

Abstract: Aggregation of nanofiller in polymer matrix is the key barrier to enhance the mechanical and thermal properties of polymer nanocomposites. Here, we report a novel vane mixer based on elongation flow processing, which is facial to achieve the homogeneous dispersion of functional graphene oxide sheets (FGs) in isotactic polypropylene (iPP). Scanning electron microscopy reveals that FGs in iPP matrix are fully exfoliated and uniformly dispersed. The crystallization behavior, mechanical properties and thermal stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…These new nanocomposites have been obtained by extrusion, in most cases twin-screw extrusion, which can be followed by injection molding. Table 2 shows that polypropylene (PP) matrix has been most commonly used [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] due to its availability and ease of processing. The effect of the concentration of nanofillers is a key parameter in the processing of nanocomposites.…”
Section: Thermoplastic Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…These new nanocomposites have been obtained by extrusion, in most cases twin-screw extrusion, which can be followed by injection molding. Table 2 shows that polypropylene (PP) matrix has been most commonly used [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] due to its availability and ease of processing. The effect of the concentration of nanofillers is a key parameter in the processing of nanocomposites.…”
Section: Thermoplastic Nanocompositesmentioning
confidence: 99%
“…% was obtained by compression molding, thus increasing electrical conductivity. In order to avoid agglomeration of the nanofiller, elongation flow processing for the dispersion of GO sheets in isotactic PP has been employed [50]. The more effective dispersion of the nanophases led to the increase of the thermal stability and mechanical properties of the nanocomposites with increasing GO content.…”
Section: Thermoplastic Nanocompositesmentioning
confidence: 99%
“…[196,197] Besides, they have good barrier effect and huge specific surface adsorption ability that helping the decrease in heat and mass transfer. [51] Furthermore, Yuan et al showed the effectiveness of application of RGO at low loadings of 0.5 to 1 wt% in RGO/iPP composites to reduce the heat and smoke release because of the improvement of swelling of char which cause the superior in isolation of char. Furthermore, the compactness of char for RGO/iPP composites was improved based on the observation from morphology of char residues.…”
Section: Flame Retardancymentioning
confidence: 99%
“…As reinforcements, different microfillers in the shape of fibers [ 1 , 2 , 3 ], powders [ 4 , 5 ], or nanofillers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ] are used. Metal particles, ceramic powders or fibers, and natural fibers are widely applied as reinforcements as well.…”
Section: Introductionmentioning
confidence: 99%